2016
DOI: 10.2217/fvl-2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hcv Treatment in People Who Actively Inject Drugs

Abstract: Aim: HCV treatment in people who actively inject drugs (PWID) (active PWID) is sometimes withheld. We propose that active PWID can be treated for HCV in the right setting. Methods: HCV-infected active PWID were evaluated at a multidisciplinary clinic in an observational study. The primary end point was a sustained virologic response following HCV therapy. Results: We included 40 active PWID, of which 63% used heroin, 70% used cocaine and 37% received all-oral regimens. With a mean follow-up of 570 days, 78% su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…For example, the C-EDGE CO-STAR study only enrolled patients on OST who had a documented compliance to appointments of at least 80% [ 12 ]. However, recent real-world studies have demonstrated that low loss-to-follow-up rates and high SVR rates (exceeding 90%) can be achieved in PWIDs receiving integrated care from multidisciplinary teams [ 23 , 24 ], and that rates of treatment completion and SVR comparable with the general patient population can be achieved in active drug users and patients receiving OST [ 25 ]. These findings support the provision of DAA therapy to such patients, the treatment of whom is key to achieving the goal of elimination of HCV transmission [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the C-EDGE CO-STAR study only enrolled patients on OST who had a documented compliance to appointments of at least 80% [ 12 ]. However, recent real-world studies have demonstrated that low loss-to-follow-up rates and high SVR rates (exceeding 90%) can be achieved in PWIDs receiving integrated care from multidisciplinary teams [ 23 , 24 ], and that rates of treatment completion and SVR comparable with the general patient population can be achieved in active drug users and patients receiving OST [ 25 ]. These findings support the provision of DAA therapy to such patients, the treatment of whom is key to achieving the goal of elimination of HCV transmission [ 25 ].…”
Section: Discussionmentioning
confidence: 99%